Market complicity and Christian ethics - Barrera, Albino (Cambridge, UK ; New York : Cambridge University Press, 2011)
"The marketplace is a remarkable social institution that has greatly extended our reach so shoppers in the West can now buy fresh-cut flowers, vegetables, and tropical fruits grown halfway across the globe even in the depths of winter. However, these expanded choices have also come with considerable moral responsibilities as our economic decisions can have far-reaching effects by either ennobling or debasing human lives. Albino Barrera examines our own moral responsibilities for the distant harms of our market transactions from a Christian viewpoint, identifying how the market's division of labour makes us unwitting collaborators in others' wrongdoing and in collective ills. His important account covers a range of different subjects, including law, economics, philosophy, and theology, in order to identify the injurious ripple effects of our market activities"--
"Christian ethics has increasingly assumed a central place within academic theology. At the same time the growing power and ambiguity of modern science and the rising dissatisfaction within the social sciences about claims to value-neutrality have prompted renewed interest in ethics within the secular academic world. There is, therefore, a need for studies in Christian ethics which, as well as being concerned with the relevance of Christian ethics to the present-day secular debate, are well informed about parallel discussions in recent philosophy, science or social science"--
Part I. Theory: Material Cooperation in Economic Life: 1. The nature of material cooperation and moral complicity; 2. Complicity in what?: the problem of accumulative harms; 3. Too small and morally insignificant?: the problem of overdetermination; 4. Who is morally responsible in the chain of causation?: the problem of interdependence -- Part II. Application: A Typology of Market-Mediated Complicity: 5. Hard complicity I: benefiting from and enabling wrongdoing; 6. Hard complicity II: precipitating gratuitous accumulative harms; 7. Soft complicity I: leaving severe pecuniary externalities unattended; 8. Sofr complicity II: reinforcing injurious socioeconomic structures -- Part III. Synthesis and Conclusions: 9. Toward a theology of economic responsibility; 10. Synthesis: Christian ethics and blameworthy material cooperation.
Includes bibliographical references (p. 286-299) and index.
Description based on print version record.
Keywords: Christian ethics; RELIGION / Christian Theology / Ethics; Electronic books